Pain, anxiety and patient satisfaction in office hysteroscopy, is there a link? Are patient satisfaction questionnaires reliable? - Paulo, Antonio A.; Pipa, Antonio; Andrade, Claudia Raquel; Oliveira, Raquel; Afreixo, Vera M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Office hysteroscopy is becoming increasingly popular leading to examinations and operations without anesthesia. Anxiety is always present before an aversive medical intervention and may play a role in pain perception. The objectives of the study were to determine if pain perception is linked to anxiety and how well patient satisfaction questionnaires correlate with pain. Methods: Prospective observational study enrolled one hundred and four women. One hundred cases were included and analyzed. Patients scheduled for office hysteroscopy, who accepted to participate and were able to answer questionnaires. Results: A ten centimeter visual analogue scale was used for pain evaluation and the State anxiety-trait inventory for adults questionnaires for anxiety assessment. Three other satisfaction questionnaires, each consisting of three answers, were also administered and investigated. Analysis was performed using SPSS 22.0 IBM for windows software tools. Conclusions: Correlation between anxiety and pain reporting showed no influence with anxiety trait (p value = 0.4170) and a mild correlation with anxiety state (p value = 0.146). Classification of pain into “no pain”, “mild pain”, “moderate pain” and “severe pain”, should be revised in office hysteroscopy: for visual analogue scale, scores of 2.5 to 3 cm correspond to the lower boundary of moderate pain and scores above limit 6.5 cm should define pain as severe. Satisfaction questionnaires significantly correlated to discomfort (p value <0.001) and may be a practical option to assess tolerance of medical procedures with excellent sensibility and specificity.